2020
DOI: 10.3390/aerospace7070085
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Elements of an Urban UTM

Abstract: Urban airspace environments present exciting new opportunities for delivering drone services to an increasingly large global market, including: information gathering; package delivery; air-taxi services. A key challenge is how to model airspace environments over densely populated urban spaces, coupled with the design and development of scalable traffic management systems that may need to handle potentially hundreds to thousands of drone movements per hour. This paper explores the background to Urban un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…We present a perspective model for urban airspace segmentation and multilayer airspace, as shown in Figure3. In each layer, airways (or safety tubes) and nodes are designed such that the aircraft can operate in the specified layers for mobility [8]. The airways are aircraft corridors linked with nodes at each intersection within a layer horizontally or between layers vertically or even diagonally.…”
Section: ) Multilayer Airspace Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We present a perspective model for urban airspace segmentation and multilayer airspace, as shown in Figure3. In each layer, airways (or safety tubes) and nodes are designed such that the aircraft can operate in the specified layers for mobility [8]. The airways are aircraft corridors linked with nodes at each intersection within a layer horizontally or between layers vertically or even diagonally.…”
Section: ) Multilayer Airspace Modelmentioning
confidence: 99%
“…The different layers allow various aircraft to fly in the designated layers at varying speed levels. The aircraft speed increases with altitude as there will be few or no static obstacles at higher altitudes; hence, airway highways are feasible [8]. Thus, UAVs and PAVs can fly at different attitudes and destinations at various speeds in their designated safety tubes minimizing collisions between aircraft.…”
Section: ) Multilayer Airspace Modelmentioning
confidence: 99%
“…Many articles were found that reported investigations of the technical mechanisms, procedures, and regulations by which shared airspace might be realised, particularly with respect to the development of UTM, which is by far the predominant concept in the domain. McCarthy et al [19] investigated contemporary shared airspace research including initiatives in both the USA and Europe, and identified proposed approaches to expedite UTM solutions for urban areas such as drone certification schemes, collaborative and democratic airspace design, development of scalable traffic management solutions, and the replacement of humans with machines in operating and coordinating drone traffic. Capitán et al [12] reported the development of a software architecture for UTM that can provide real-time monitoring of airspace to enable tactical de-confliction and management of emergencies.…”
Section: Drone Industry Attitudes To Shared Airspacementioning
confidence: 99%
“…Some have suggested single altitude lane-based approaches that primarily investigated trajectory scheduling algorithms in a way to tackle strategic conflict management [14,15]. While others have focused on conceptual design studies into the use of airway routes over buildings, railways and roads for the city of Singapore [16,17], a majority of the work has been centred on policy-based studies for Europe's advanced air mobility traffic management program, U-Space [18][19][20][21]. However, the common thread in these studies is that they are mainly limited to very low traffic densities of drones or even single drone flight operations.…”
Section: Introductionmentioning
confidence: 99%